LIFE- CYCLE ASSESSMENT OF THE ENVIRONMENTAL IMPACT ASSESSMENT OF THE MINING INDUSTRY IN MONGOLIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The mining industry is growing rapidly it is important to the national economy of Mongolia.On the other hand, the extraction and processing of mining industries involve particle emission to air or water, toxicity to the environment, contamination of water resources and most importantly decay of human health. The mining industries increase their GDP significantly. However, the most important problem is making the mining  Mongolia country sustainable thus reducing the emissions. The main mining industry product includes copper, gold and other minerals. The aim of the study is the application of LCA in the mining industry. To address the environmental impacts caused by the mining sectors in Mongolia, this research is going to analyze the environmental impacts caused by the 3 major minerals extraction processes, which are copper and gold, coal by using the life-cycle impact assessment technologies. This paper presents a review of the current application of LCA in the mining industry. In the results section, SimaPro software version 8.4 using ReCipe and GaBi 4.0™ LCA software was used.